Effects of resveratrol, piceatannol and quercetin in an equine cartilage explant model for potential use in treating osteoarthritis - Islam, Purba (2019)
Currently there are no disease-modifying osteoarthritis drugs (DMOADs) available and the treatment for osteoarthritis (OA) is still based on minimising symptoms. Commonly used drugs for OA have health hazards from long and short term use and has led to patients using alternatives therapies such as nutraceuticals.